Water quality parameters of six selected oxbow lakes (baors) in Bangladesh - Chowdhury, Gawsia W; Bulbul, Mosammat Sharmin; Sarker, Bhakta Supratim (Dhaka University Journal of Biological Sciences, 2016)
Abstract not available Dhaka Univ. J. Biol. Sci. 25(1): 91-95, 2016